ANALYSIS OF THE IMAGES CREATED BY THE POET IN THE MODIFICATION OF THE SPIRITUAL WORLD - Yallayev Bekzod (International Journal of Literature and Language Studies, 2026)
In this article it is expressed poetic features of the poetry by Tilak Jo‘ra, sincerity in the poet’s senses, his fanciest viewpoints about the world and man. Especially, contradiction between a word and spirit, feelings of soul in metaphorical interpretation is expressed and poetic meaning layers emerge as interpretations based on the plot.